PROFIL BERPIKIR KRITIS SISWA KELAS X-IPA 3 MAN 2 JEMBER BERDASARKAN GENDER DALAM MENYELESAIKAN SOAL MATEMATIKA POKOK BAHASAN SISTEM PERSAMAAN LINIER TIGA VARIABEL - Trapsilasiswi, Dinawati; Pratiwi, Anggun Ika; Susanto, Susanto (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research describe the profile of critical thinking based on gender in solving sytems of linear equation with three variables problems at X-IPA 3 MAN 2 Jember. Critical thinking standards which are used in this research are: focus, reason, inference, situation, clarity, and overview. Instruments that are used are contextual mathematics problems and interview guidlines. Subject of this research are all of the students in X-IPA 3 MAN 2 Jember, six students that are interviewed consists of 3 male students and 3 female students. Male students fulfilled tend 5 standards of critical thinking which are focus, reason, inference, situation, and clarity. They tend not writing which method that is used by them when working on the problems, however when interviewed they can explain method which is used to solve the problem, can make a conclusion for every problems well and could use every information to solve the problems. Female students fulfilled 5 stadards of critical thinking which are focus, reason, inference, situation, and clarity. They can understand the problem well, can write down what are given in the problems, things asked, and method which is used to solve the problem, could make a conclusion for every problems given, and could use every information to solve the problems. Keywords : Critical Thinking, Gender, and Linear Equation System Of Three Variables